A MODULAR DESIGN OF A WALL-CLIMBING ROBOT AND ITS MECHATRONICS CONTROLLER - Tlale, N.S. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The modular design of a wall-climbing robot, implementing two articulated legs per module (biped robotic modules), is presented in this paper. Modular design improves a wall-climbing robot